"صاحبزاده ميان محمدي بن ميان عمر : حياته، خدماته وآثاره العلمية۔ Sahibzada Mian Muhammadi Son of Mian Umer: His Life, Contributions and Academic Effects " - Faisal Mahmood (الإيضاح, 2017)
"Mian Muhammadi (son of Hazrat Mian Umer) was a great sufi saint and Islamic scholar of Khyber Pakhtunkhwa Pakistan in 19th century and born in a well known village “Chamkani” of district Peshawar. He was a multi dimensional personality of his time being a saint respectful to the all sects of Muslims, as a poet of Arabic and Pashto, and a scholar having a systematic program for publication of the books. He has authored a number of books in various fields of Islamic Studies and Shariah adopting a unique methodology in writing. He, the Mian Muhammadi, has spent his whole life in quenching the spiritual thirst of the local Muslim of that era on one hand, and spreading the knowledge on other hand. In the present paper, personal life, services as well as academic effects of this great saint have been discussed scholarly in order to bring forth his life sketch and contributions before the scholars."